Chronic Urticaria: Indian Context—Challenges and Treatment Options - Sujoy Khan; Anirban Maitra; Pravin Hissaria; Sitesh Roy; Mahesh Padukudru Anand; Nalin Nag; Harpal Singh (Dermatology Research and Practice)
Urticaria is a common condition that occurs in both children and adults. Most cases have no specific allergic trigger and the aetiology of urticaria remains idiopathic and occasionally spontaneous in nature. Inappropriate advice such as avoidance of foods (milk, egg, prawn, and brinjal) is common place in certain sections of India mostly by nonspecialists that should not be routinely recommended. It is important to look for physical urticarias such as pressure urticaria in chronic cases, which may be present either alone or in combination with other causes. Autoimmune causes for chronic urticaria have been found to play an important role in a significant proportion of patients. Long-acting nonsedating antihistamines at higher than the standard doses is safe and effective. Quality of life is affected adversely in patients with chronic symptomatic urticaria and some may require multidisciplinary management.